RANCANGAN LEARNING MANAGEMENT SYSTEM BERBASIS WEB (STUDI KASUS PADA SDN CAWANG 09 JAKARTA TIMUR) - Nur Frisca Rossy Permata, (2023)
Learning management system is a medium in creating or distributing knowledge in a structured way. Cawang 09 Jakarta State Elementary School is an official government educational institution that has used a curriculum in accordance with applicable recommendations. However, in the business process, SDN Cawang 09 Jakarta does not yet have a system that can manage teaching materials for educators. This causes difficulties for educators in finding the material needed. Therefore, the researcher aims to design a web-based learning management system that can be used by educators and students to collect, manage, and distribute educational materials. In this paper, researchers used a data collection process using observation, interview and literature study techniques. The learning management system that will be designed uses the RAD method for system development. The result of this research is a Learning Management System Design that can be used by educators and students in terms of obtaining, collecting and distributing materials, assignments, quizzes, forums, and exams in the process of organizing learning in SD Cawang 09 which functions as a documentation medium.